新sat试题下载【OG数学真题】!新SAT数学相比改革之前难度有所增加,所以在新SAT数学备考期间考生需要通过有效的练习,掌握新SAT数学考察知识点,下面智课网为大家精选了新SAT数学OG真题,大家可以做下练习。

  新satOG数学真题精选:

  1.Which of the following expressions is equal to 0 for some value of x?

  A . ∣x−1∣−1∣x−1∣−1

  B . ∣x+1∣+1∣x+1∣+1

  C . ∣1−x∣+1∣1−x∣+1

  D . ∣x−1∣+1

  答案解析

  Choice A is correct.

  The expression ∣x−1∣−1∣x−1∣−1 will equal 0 if midx−1∣=1midx−1∣=1. This is true for x=2x=2 and for x=0x=0. For example, substituting x=2x=2 into the expression ∣x−1∣−1∣x−1∣−1 and simplifying the result yields ∣2−1∣−1=∣1∣−1=1−1=0∣2−1∣−1=∣1∣−1=1−1=0. Therefore, there is a value of x for which ∣x−1∣−1∣x−1∣−1 is equal to 0.

  Choice В is incorrect. By definition, the absolute value of any expression is a nonnegative number. Substituting any value for xx into the expression ∣x+1∣∣x+1∣ will yield a nonnegative number as the result. Because the sum of a nonnegative number and a positive number is positive, ∣x+1∣+1∣x+1∣+1 will be a positive number for any value of xx. Therefore, ∣x+1∣+1≠0∣x+1∣+1≠0 for any value of xx. Choice С is incorrect. By definition, the absolute value of any expression is a nonnegative number. Substituting any value for xx into the expression ∣1−x∣∣1−x∣ will yield a nonnegative number as the result. Because the sum of a nonnegative number and a positive number is positive, ∣1−x∣+1∣1−x∣+1 will be a positive number for any value of xx. Therefore, ∣x−1∣+1≠0∣x−1∣+1≠0 for any value of xx. Choice D is incorrect. By definition, the absolute value of any expression is a nonnegative number. Substituting any value for x into the expression ∣x−1∣∣x−1∣ will yield a nonnegative number as the result. Because the sum of a nonnegative number and a positive number is positive, ∣x−1∣+1∣x−1∣+1 will be a positive number for any value of xx. Therefore, ∣x−1∣+1≠0∣x−1∣+1≠0 for any value of xx.

  2.新sat试题下载

  3.If f(x)=−2x+5f(x)=−2x+5, what is f(−3x)f(−3x) equal to?

  A . −6x−5−6x−5

  B . 6x+56x+5

  C . 6x−56x−5

  D . 6x2−15x6x2−15x

  答案解析

  Choice В is correct.

  If f(x)=−2x+5f(x)=−2x+5, then one can evaluate f(−3x)f(−3x) by substituting −3x−3x for every instance of xx. This yields f(−3х)=−2(−3x)+5f(−3х)=−2(−3x)+5, which simplifies to 6x+56x+5.

  Choices A, C, and D are incorrect and may be the result of miscalculations in the substitution or of misunderstandings of how to evaluate f(−3x)f(−3x).

  以上是智课网为大家精选的新SAT官方指南真题及答案解析,欢迎考生下载新SAT数学官方指南完整套题,方便在备考中使用。

展开显示全文